Comparing intake and digestibility of Ficus benjamina and Carica papaya L. by Philippines glossy starling, aplonis panayensis - Kannan, Karupaya (Universiti Malaysia Sarawak (UNIMAS), 2007)
The intake and digestibility of Ficus benjamina and Carica papaya L. by Philippines Glossy Starling, Aplonis panayensis was studied using ten birds per treatment. They were fed with the test-diet ad IIbitilim for 14 days and first seven days were used as adjustment days in captivity. The amount of food given, left-over and feaces were collected daily and dried to calculate the dry matter intake and digestibility. The result showed that dry matter intake and digestibiJity of C. papaya is higher than F. benjamina by Philippines Glossy Starling. The body weight loss also was at minimum level by birds consuming C. papaya diet.